Position of Contract Marriage in View of Islamic Law (Challenges and Dynamics in Bogor Regency) - Tolkah (Journal of Law Science, 2019)
Marriage is an obligation that will involve two human men and women, in this process, of course, every couple wants an eternal and lasting bond and avoids the act of divorce which is strictly prohibited in religion. But in practice every marriage relationship certainly has a risk that can break the ties leading to a deviation. In Indonesia, there is a form of marriage irregularity in several areas, one of which is in Bogor Regency. This case is called a contract marriage or in the teachings of the Islamic religion it is often called a muth'ah marriage, in the process of mut'ah marriage or in Indonesia itself it is called a contract marriage which has very limited regulations and is also very far from Islamic religious law.